Outcomes and factors by risk group after prostate brachytherapy: Cohort study in 2316 patients - Katayama , Norihisa; Nakamura , Katsumasa; Yorozu , Atsunori; Kikuchi , Takashi; Magome , Taiki; Saito , Shiro (Seram, 2021)
PURPOSE: To evaluate bFFF by risk group and treatment modality and the predictive factors of bFFF by risk group in patients with prostate cancer undergoing permanent seed implantation (PI) ± external beam radiation therapy (EBRT) in a nationwide prospective cohort study in Japan (J-POPS) during the first 2 years. METHODS AND MATERIALS: The analyses included 2,316 participants. BFFF was evaluated using the Phoenix definition. The Cox proportional hazards model was used to identify the factors associated with bFFF. RESULTS: Median follow-up period was 60.0 months. The 5-year bFFF rates in all patients, 1,028 low-risk patients, 1,114 intermediate-risk patients, and 133 high-risk patients were 93.6%, 94.9%, 92.7%, and 91.1%, respectively. The 5-year bFFF rates in the PI group and EBRT combination therapy group were 93.7% and 93.3%, respectively. In a multivariate analysis, younger age, higher Gleason score (GS), higher percent positive biopsies (%PB), and lower prostate V100 (p=0.0012, 0.0030, 0.0026, and 0.0368) in all patients; younger age, higher pretreatment prostate-specific antigen (PSA), and lower prostate V100 (p=0.0002, 0.0048, and 0.0012) in low-risk patients; higher GS, higher %PB, and no hormonal treatment (p=0.0005, 0.0120, and 0.0022) in intermediate-risk patients; and higher GS and higher %PB (p=0.0329 and 0.0120) in high-risk patients were significantly associated with bFFF. CONCLUSIONS: PI ± EBRT resulted in excellent short-term biochemical outcomes in all risk groups, especially in high-risk patients. Age, pretreatment PSA, and prostate V100 in low-risk patients; GS, %PB, and hormonal treatment in intermediate-risk patients; and GS and %PB in high-risk patients were independently affected bFFF.